2018
DOI: 10.1002/hyp.11437
|View full text |Cite
|
Sign up to set email alerts
|

The morpho‐textural signature of large bedforms in ephemeral gravel‐bed channels of various planforms

Abstract: This study adopts a fresh approach to find the similarities between river planforms in contrast to many previous studies that have presented distinguishing characteristics and thresholds. This new approach links textural and morphological attributes of bedforms, termed morpho‐texture, with process and hydrological regime thereby indicated. The study was carried out in depositional features of ephemeral rivers having a range of planforms and located in the Judean Desert. High‐resolution terrestrial laser scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
(203 reference statements)
0
4
0
Order By: Relevance
“…Photographic or 'photosieving' methods include those that analyse image texture using semivariograms (Carbonneau et al, 2004;Verdú et al, 2005;Black et al, 2014), analyse image intensity by autocorrelation (Rubin, 2004;Barnard et al, 2007), identify individual grains (Graham et al, 2005), and use Fourier-optics principles (Buscombe and Rubin, 2012). Alternative approaches have used high-resolution digital elevation models (DEMs) from terrestrial laser scanning (TLS; Heritage and Milan, 2009;Hodge et al, 2009;Brasington et al, 2012;Baewert et al, 2014;Schneider et al, 2015;Storz-Peretz and Laronne, 2018) and Structure-from-Motion surveys (Westoby et al, 2015;Vázquez-Tarrío et al, 2017;Woodget and Austrums, 2017) to derive relationships between topographic roughness (i.e. the vertical variation in elevation) and grainsize.…”
Section: Introductionmentioning
confidence: 99%
“…Photographic or 'photosieving' methods include those that analyse image texture using semivariograms (Carbonneau et al, 2004;Verdú et al, 2005;Black et al, 2014), analyse image intensity by autocorrelation (Rubin, 2004;Barnard et al, 2007), identify individual grains (Graham et al, 2005), and use Fourier-optics principles (Buscombe and Rubin, 2012). Alternative approaches have used high-resolution digital elevation models (DEMs) from terrestrial laser scanning (TLS; Heritage and Milan, 2009;Hodge et al, 2009;Brasington et al, 2012;Baewert et al, 2014;Schneider et al, 2015;Storz-Peretz and Laronne, 2018) and Structure-from-Motion surveys (Westoby et al, 2015;Vázquez-Tarrío et al, 2017;Woodget and Austrums, 2017) to derive relationships between topographic roughness (i.e. the vertical variation in elevation) and grainsize.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the recent development of new high‐resolution topographic methods has exponentially increased our capacity for spatially distributed characterizations of topography (Wheaton et al., 2015) and grain size in gravel rivers (Vazquez‐Tarrio et al., 2017). These methods provide new clues for the analysis of reach‐scale spatial variability in the topographic and grain‐size parameters needed for sediment‐transport modeling (see, for example, Storz‐Peretz and Laronne (2013, 2018)).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that bedload particles' moving and resting states have significant associations with the surface structure of the riverbed (Pyrce & Ashmore, 2005; Storz‐Peretz & Laronne, 2018). The bedload transport behavior is closely related to the bedform.…”
Section: Laboratory Experimentsmentioning
confidence: 99%